Unattainable Unity or Two Models of Ecumenism - Kopania, Jerzy (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The term ecumenism is used to refer to initiatives aimed at uniting all Christians into one common Church. The ecumenical movement originated at the beginning of the 19th century in Protestant and Anglican Churches. At that time the Catholic Church believed it to be the result of misguided understanding of theological concepts. This early attitude of the Catholic Church was expressed by Pope Pius XI in his 1928 encyclical Mortalium animos. The major change of attitude came with the Second Vatican Council: the 1964 Decree on ecumenism Unitatis redintegratio brought a new interpretation of the concept, an interpretation which may seem contradictory to the previous one. This paper argues that the two documents are not in fact contradictory, but present two models of ecumenism. However, neither of them can be implemented. This impossibility cannot be avoided because it is inherent in the metaphysical nature of this world and the nature of man who belongs to it.